Do Self-Efficacy, Body Mass Index, Duration Of Onset And Pain Intensity Determine Performance On Selected Physical Tasks In Individuals With Unilateral Knee Osteoarthritis? - Adegoke, B.O.A.; Boyinde, O.H.; Odole, A.C.; Akosile (Musculoskeletal Science and Practice, 2017)
Purpose: To investigate the contributions of Pain Self-Efficacy (PSE), Function Self-Efficacy (FSE), Body Mass Index (BMI), duration of onset of Knee OsteoArthritis (KOA) and Present Pain Intensity (PPI) to performance on Stair Task Test (STT), Timed Up-and-Go (TUG) and 20-Meter Walk Test (20-MWT) and explore correlations among the variables in individuals with unilateral KOA. Methods: Participants were 51 (22 male, 29 female) consecutively-selected patients with unilateral KOA. Participants' self-efficacy (PSE, FSE), and PPI were assessed using Arthritis Self-Efficacy Scale and Box Numerical pain scale respectively. Participants' performance on STT, TUG and 20-MWT was also assessed. Data were analyzed with Pearson product moment correlation and Stepwise linear regression at alpha level of 0.05. Results: Participants' mean age, duration of KOA onset and BMI were 52.18 ± 10.69 years, 30.29 ± 29.03months and 26.06 ± 3.86 kg/m2 respectively. Participants' scores on 20MWT, TUG and STT had significant direct correlations with each other and with PPI while PPI had significant indirect cor relations with PSE (r ¼ 0.59) and FSE (r ¼ 0.56). PSE had significant direct correlation (r ¼ 0.65) with FSE. Both PSE and FSE had significant but low inverse correlations with scores on the performance tests. PPI explained about 43% or more of the variance in 20-MWT, TUG and STT. PPI and onset of KOA explained 62% of variance in 20-MWT while PPI and BMI jointly explained 60% of variance in TUG. Conclusion: Though PSE and FSE significantly correlated with scores on the performance tests, PPI, duration of OA and BMI were the significant determinants of performance.
Research Article
Keywords: Knee osteoarthritis; Self-efficacy; Physical function; Pain intensity